2015
DOI: 10.1007/s10278-014-9757-1
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Immune System-Based Support Vector Machine Approach for Classifying Ultrasound Breast Tumor Images

Abstract: A rapid and highly accurate diagnostic tool for distinguishing benign tumors from malignant ones is required owing to the high incidence of breast cancer. Although various computer-aided diagnosis (CAD) systems have been developed to interpret ultrasound images of breast tumors, feature selection and the setting of parameters are still essential to classification accuracy and the minimization of computational complexity. This work develops a highly accurate CAD system that is based on a support vector machine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…GLCM (9, 10), wavelet, shearlet and curvelet (10), contourlet (10), auto-covariance matrix (12) and a combination of texture features (10,24). Results of the current study have also indicated that RLM texture analysis possesses significantly more discriminative ability than other methods, such as morphology and elastography (9,12,(20)(21)(22). Likewise, the proposed method has demonstrated a more reliable performance in comparison with previous studies that combined texture and morphological features (9,12).…”
supporting
confidence: 53%
See 2 more Smart Citations
“…GLCM (9, 10), wavelet, shearlet and curvelet (10), contourlet (10), auto-covariance matrix (12) and a combination of texture features (10,24). Results of the current study have also indicated that RLM texture analysis possesses significantly more discriminative ability than other methods, such as morphology and elastography (9,12,(20)(21)(22). Likewise, the proposed method has demonstrated a more reliable performance in comparison with previous studies that combined texture and morphological features (9,12).…”
supporting
confidence: 53%
“…Wu et al (12) has combined texture and morphological features from ultrasound images and indicated that combined features gained better for classifying breast tumors with a sensitivity, specificity and accuracy of 96.67%, PPV of 95.6%, NPV of 97.48%, and A z of 0.9827. In a Moon et al study (9), how-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous new methods of Quantitative Ultrasound (QUS) dedicated to the estimation of the structural changes in tissue are being developed (Mamou, Oelze, 2013; Wu et al, 2015). Particularly, analysis of statistical properties of the backscattered radiofrequency (RF) signals have been successfully applied to differentiate healthy tissue from tissue regions changed pathologically (Nowicki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The classifier is a tool that provides as output the risk degree related to the tissue. Classifiers like support vector machine (SVM) [5,6,12,13], decision tree [5], neural network [5,11], and linear discriminant analysis (LDA) [5,14] have been widely used and performed well. Wu et al [6] segmented the breast tumor by level set method, and the auto-covariance texture features and morphologic features were extracted, then they used the genetic algorithm to detect the significant features and identified the tumors by SVM, which get the accuracy of 95.24 %.…”
Section: Introductionmentioning
confidence: 99%